PREDICTING SKINCARE SALES OF ORIGINAL MS GLOW WITH SES METHOD - Ariska, Feby; Rizaldi, Rizaldi; Sumantri, Sumantri (Universitas Royal, 2025)
Abstract: Ms Glow Kisaran Original Store is one of the beauty companies that sells skincare products that are useful for maintaining healthy facial and body skin. However, the Original Ms. Glow series currently faces challenges such as tight competition and ineffective inventory management in terms of sales figures. This company sells ± 1500 products a month, but also often faces shortages and stockpiles of product, which can reduce customer confidence and cause Ms. Glow Kisaran Original to experience financial losses, among others. Conversely, if the demand for skincare increases but the skincare supply cannot be prepared, this is a loss for the store and customers. The purpose of this study is to improve the accuracy of the forecast, the use of the Single Exponential Smoothing Method is proposed. This method smoothes past values with exponential weights, placing greater emphasis on the latest data. The use of data from the last 12 months as reference data for past recording for forecasting experiments for the next 1 (one) month. The results of the study at Ms Glow Kisaran show the flexibility of the method in adapting to different sales dynamics. Overall, this research helps in predicting skincare sales predictions at the Ms Glow Kisaran Original Kisaran Store using the Single Exponentian Smoothing method, so that it can overcome the challenges in predicting sales figures.Keywords: ms glow kisaran; skincare sales; ses. Abstrak: Toko Ms Glow Kisaran Original merupakan salah satu perusahaan di bidang kecantikan yang menjual produk-produk skincare yang bermanfaat untuk menjaga kesehatan kulit wajah dan tubuh. Namun rangkaian Original Ms. Glow saat ini menghadapi tantangan seperti persaingan yang ketat dan pengelolaan inventaris yang kurang efektif dalam hal angka penjualan. Perusahaan ini menjual ±1500 produk dalam sebulan, namun juga sering menghadapi kekurangan dan penumpukan stok produk, yang dapat menurunkan kepercayaan pelanggan dan menyebabkan Ms. Glow Kisaran Original mengalami kerugian finansial. Sebaliknya jika permintaan akan skincare meningkat namun persediaan skincare tidak dapat disiapkan maka ini menjadi kerugian bagi pihak toko dan pelanggan. Tujuan penelitian ini adalah untuk meningkatkan ketepatan perkiraan, penggunaan Metode Single Exponential Smoothing diusulkan. Metode ini menghaluskan nilai masa lalu dengan bobot eksponensial, memberikan penekanan lebih besar pada data terbaru. Penggunaan data 12 bulan terakhir sebagai data acuan pencatatan masa lalu untuk percobaan peramalan untuk 1 (satu) bulan kedepan. Hasil penelitian pada Ms Glow Kisaran menunjukkan fleksibilitas metode dalam menyesuaikan diri dengan dinamika penjualan yang berbeda. Secara keseluruhan, Penelitian ini membantu dalam meramalkan prediksi penjualan skincare di Toko Ms glow Kisaran Original Kisaran menggunakan metode Single Exponentian Smoothing, sehingga dapat mengatasi tantangan dalam memprediksi angka penjualan.Kata kunci: ms glow kisaran; penjualan skincare; ses.